2019
DOI: 10.1155/2019/9276839
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Ultrahigh‐Performance Fiber‐Reinforced Concrete Thin‐Walled Arch Subjected to Asymmetric Load

Abstract: Ultrahigh-performance fiber-reinforced concrete (UHPFRC) is an innovative material in the field of bridge engineering. With superior mechanical characteristics, this new material reduced the structural self-weight and extended the span of modern bridges. A series of tests should be conducted to establish reliable design rules for UHPFRC structures. This paper aimed at determining the compressive behavior of UHPFRC for thin-walled arch section design and a comparison was made with a normal concrete (NC) arch. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One is used as a control, and the other two are reinforced with externally bonded strips of polymer fibers according to different schemes. Great work was done by the authors of the article [15]. Here a large series of concrete and fiber concrete arches were investigated.…”
Section: Recent Research Analysismentioning
confidence: 99%
“…One is used as a control, and the other two are reinforced with externally bonded strips of polymer fibers according to different schemes. Great work was done by the authors of the article [15]. Here a large series of concrete and fiber concrete arches were investigated.…”
Section: Recent Research Analysismentioning
confidence: 99%
“…The potential of using the cement-based material as a repair material for strengthening normal concrete (NC) bridges is promising (Feng et al, 2020;Qin et al, 2020;Zhang et al, 2021). For the concrete bridges strengthened by UHPC, the bonding performance of the UHPC-NC interface is critical to ensure the efficiency (Murthy et al, 2018;Yang et al, 2019). The literature showed that more than 50% of structures failed due to interfacial cracking after repair or reinforcement (Li, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of ultra-high performance concrete (UHPC) for the strengthening of structures has caught the attention of researchers [13]. Superior mechanical performance, excellent antiseismic property, and resistance against environmental degradation are the advantages of UHPC compared with the common concrete [14][15][16]. In the last few years, the possibility of using UHPC for the strengthening of RC structures has been investigated in beams [17][18][19][20], columns [21,22], joints [23], and shear walls [24,25], and the result has shown the effectiveness of this retrofit technique.…”
Section: Introductionmentioning
confidence: 99%